NATO Enjoys Firm Support Among Europeans. - United States. Department of State. Office of Research.; Demeri, Mary. (Tufts University. Tisch Library., 2019)
The past decade has been tumultuous for U.S. -Europe relations and for Europe itself, particularly in light of the revolutionary changes in central and eastern Europe and years of crisis in the Balkans. Despite these challenges, publics have remained positive toward NATO. More than a half-century in existence, NATO is widely and strongly supported and is still considered essential by large numbers in four key west European countries. Recent polls in Britain, France, Germany and Italy also suggest room for further convergence between Europe and the U.S. on regional and worldwide security policies.; Opinion Analysis M-197-00